In situ Combined Electrochemical Techniques for Conducting Polymers - Visy, Csaba (SpringerBriefs in Applied Sciences and Technology,, 2017)
This book outlines methods to improve functioning of these polymer based devices - in particular, the multi-faceted cognition of these materials. In situ electrochemical techniques are studied to elucidate redox switching between non-conducting and conducting states. The book examines the advantages of combinations of in situ electrochemical techniques in a hyphenated mode for analyzing conducting polymers.